ä½¿ç”¨æ±‰è¯æ‹¼éŸ³æ•™å¦æé«˜MAS RAUDHATUL ULUM 1 MERANTIé«˜ä¸ä¸€å¹´çº§çš„å¦ç”Ÿ è®¤è¯»æ±‰å—èƒ½åŠ› - Masiri, Masiri; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractHanyu Pinyin Â is a recognize letters, as an effective tool for learning Mandarin language. This study aims to improve students' ability to recognize letters in class MAS Raudhatul Ulum 1 Meranti. Hanyu Pinyin teaching process described by the descriptive study, to recognize and read Chinese characters and Pinyin. The results of data analysis showed that the use of Hanyu Pinyin can improve the students' ability to recognize letters. Through the implementation in the classroom, its proved that mastering Hanzi needs intensive training. Therefore we can say that Hanyu Pinyin is one of the important factor to recognize letters/ Hanzi.Â Keyword Â :Â Hanyu Â Pinyin Â teaching Â Hanyu Â Pinyin ability Â toÂ recognize letters